Exosomes as natural vectors for therapeutic delivery of bioactive compounds in skin diseases - Keshtkar, Somayeh; Asvar, Zahra; Najafi, Haniyeh; Heidari, Mozhdeh; Kaviani, Maryam; Sarvestani, Fatemeh Sabet; Tamaddon, Ali Mohammad; Sadati, Maryam Sadat; Hamidizadeh, Nasrin; Azarpira, Negar (Frontiers in Pharmacology, 2025)
Skin diseases are a broad category of diseases and each has complex conditions, which makes it challenging for dermatologists to provide targeted treatment. Exosomes are natural vesicles secreted by cells and play a key role in cell communication. Due to their unique characteristics, including inherent stability, minimal immunogenicity, high biocompatibility, and exceptional ability to penetrate cells, exosomes are being explored as potential delivery vehicles for therapeutics across various diseases including skin problems. Utilizing exosomes for drug delivery in skin diseases can improve treatment outcomes and reduce the side effects of traditional drug delivery methods. Indeed, exosomes can be engineered or utilized as an innovative approach to deliver therapeutic agents such as small molecule drugs, genes, or proteins specifically to affected skin cells. In addition to targeting specific skin cells or tissues, these engineered exosome-based nanocarriers can reduce off-target effects and improve drug efficacy. Hence, this article highlights the transformative potential of this technology in revolutionizing drug delivery in dermatology and improving patient outcomes.